Perbandingan Fonologi Pada Bahasa Indonesia Dan Bahasa Jepang - Asti Dwi Ananta; Dinda Febrian; Nazwa Nadzilah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
Phonology is a branch of linguistics that studies the sound system of language and examines the rules that regulate the use of language sounds based on their characteristics, such as articulation, frequency, duration, and intensity. This research discusses "Phonological Differences in Indonesian and Japanese." The aim of this research is to obtain data and information about the differences in phonology between Indonesian and Japanese. The research method used is a literature study by collecting scientific articles and journals from various relevant sources as material for comparative analysis between the phonological systems of Indonesian and Japanese. The findings of this research indicate that there are significant differences between the phonologies of Indonesian and Japanese. The implication of this research is that it is important to understand the differences in Indonesian and Japanese phonology, which can provide benefits in teaching and learning both languages in the future.